Facial Recognition Technology: A Multinational Analysis of Regulatory Framework, Ethics, and Legal Implications in Security and Privacy - Abd. Azis DP; Andi Annisa Nurlia Mamonto; Bachrul Amiq; Khairul Mufti Rambe; Alfin Reza Syahputra (International Journal of Science and Society, 2023)
The latest technological developments allow for the presence of facial recognition technology. This technology itself is widely used in everyday life, such as for using personal devices or registering. But at the same time, the presence of this technology can cause problems with personal data. This research then aims to see the relationship between facial recognition technology and regulations, ethics, and legal implications in data security and privacy. This research will be carried out using a descriptive qualitative approach. The data used in this research was obtained through the results of relevant previous research and studies. The results of this research then found that the presence of facial recognition technology has significant benefits, but at the same time poses significant challenges. These challenges generally center around data security and privacy issues. Therefore, it is necessary to have guidelines that can regulate the use of facial technology, so that in the future this technology is not misused, and can maintain the security and privacy of society in general.